y-2/3=6

Simple and best practice solution for y-2/3=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-2/3=6 equation:



y-2/3=6
We move all terms to the left:
y-2/3-(6)=0
determiningTheFunctionDomain y-6-2/3=0
We multiply all the terms by the denominator
y*3-2-6*3=0
We add all the numbers together, and all the variables
y*3-20=0
Wy multiply elements
3y-20=0
We move all terms containing y to the left, all other terms to the right
3y=20
y=20/3
y=6+2/3

You can always share this solution

See similar equations:

| 2x+x+x+x=470 | | 4x-4=-5(7x-6)+83 | | (32/x)+6x=90 | | 32/x+6x=90 | | (-17-3r/2)=-19 | | (3-x)(4-x)-2=0 | | 1x^2-7x+2=-8 | | x4-15x2=16 | | f/4+75=158 | | 5x+13+4x+12=11x+3 | | (3x+5)/4-(2x-1)/3=2 | | 5x+13+4x+12+11x+3=180 | | 13f-72=760 | | 7f+49=434 | | 6m+21/2=33/2 | | (x+10)/2+3=2 | | x+10/2+3=2 | | 6x^2-9x-56.5=0 | | 33/2x-5-3=1/4 | | 5x+8-7x=15-17x+15x-7 | | 4(3x+4)=-4x+5 | | 6(4x-3)=9x+2 | | 5y-7+y+25=8y+20-4y | | 7c+13c=160 | | 5?(x-3)+8x=6x-5+x | | 3(1y-4)=28 | | 8.8x=44.0 | | 4x+6=-7x+1 | | 13x-9=-14 | | -7/3a=21 | | (x)+(x+1)+(x+2)=42 | | 3t2=16t-5 |

Equations solver categories